Experimental investigations on fairness and social norms in allocation settings - Schmidt, Robert J. (2020)
The research agenda that guides this dissertation is characterized by the three aspects specified in the title. First, all of the projects are experimental investigations. That is, I apply the method of incentivized economic experiments in order to answer research questions through the generation of behavioral data in the "laboratory". Second, all of the experiments involve the elicitation of fairness perceptions or perceptions of social norms. Third, the experimental paradigms used in the projects represent allocation settings, where some active individuals decide about how resources are allocated, while some passive subjects depend on these decisions. Finally, the majority of the projects is connected through a methodological aspect, since most of the experiments contain coordination games, through which I try to draw inferences about the subjects´ traits on the individual level. The combined data of the projects indicate large potential to apply coordination games as an incentivized crowd wisdom device and to use coordination choices on the individual level as a tractable tool to extract private information.
Keywords: Graue Literatur; Hochschulschrift